A Testing of Prophetic Creative Thinking Model on Felo Muda Dakwah (FMD), Yayasan Dakwah Islamiah Malaysia (YADIM) - Mohd Azmir Mohd Nizah; Adibah Sulaiman @ Mohamad (Human Resources Management Academic Research Society (HRMARS), 2025)
Indexed by ERA (Tier 2)